Axion couplings in heterotic string theory - Prateek Agrawal; Michael Nee; Mario Reig (Journal of High Energy Physics)
Abstract We study the coupling of axions to gauge bosons in heterotic string theory. The axion-gauge boson couplings in the low energy 4d theory are derived by matching mixed anomalies between higher-form global symmetries and the zero-form gauge symmetry in the 10d theory. When the standard model gauge group is embedded in a single simple group in the 10d theory — as is the case for almost all heterotic models studied in the literature — the ratio of the axion-photon coupling to the axion mass is bounded above by the QCD line. This bound is relevant for a large number of axion searches which have sensitivity to axion parameter space above this line. The discovery of an axion in these searches will rule out a large class of heterotic models, making such a signal challenging to explain within heterotic string theory.